The effects of Baduanjin exercise vs. brisk walking on physical fitness and cognition in middle-aged patients with schizophrenia: A randomized controlled trial - Chen, Chyi-Rong; Huang, Yu-Chi; Lee, Yi-Wen; Hsieh, Hui-Hsien; Lee, Yi-Chen; Lin, Keh-chung (Frontiers in Psychiatry, 2022)
Objective: Patients with schizophrenia have deficits in physical and cognitive function that may become salient in their middle ages. These deficits need active intervention to prevent functional decline. Baduanjin and brisk walking show promise as interventions in patients with schizophrenia. This study investigated the effects of Baduanjin exercise versus brisk walking in middle-aged patients with schizophrenia. Methods: In this single-blind, 2-arm, parallel, randomized controlled trial, 48 participants aged older than 40 years were enrolled and assigned to the intervention group (Baduanjin) or the control group (brisk walking). The training of both groups took place twice a week, 60 minutes per session, for 12 weeks. The participants were evaluated with physical, cognitive, and functional outcomes at baseline, postintervention, and 4 weeks after the intervention. Results: The results of the study demonstrated significant time effects in walking distance (p = 0.035, η2 = 0.094) and lower extremity strength (p = 0.006, η2 = 0.152). Post hoc analysis revealed both groups had significant improvement in changes from baseline to the postintervention assessment (ps < 0.05) and follow-up (ps < 0.05). The results demonstrated a significant group-by-time interaction in change scores of global cognition (F = 7.01, p = 0.011, η2 = 0.133). Post hoc analysis revealed a significant improvement in the Baduanjin group from baseline to postintervention (p = 0.021), but the improvements were not maintained at the follow-up assessment (p = 0.070). The results also demonstrated significant group effects in balance function (p < 0.001, η2 = 0.283), motor dual-task performance (p = 0.026, η2 = 0.103), and cognitive dual-task performance (p < 0.001, η2 = 0.307). Post hoc analysis revealed that the Baduanjin group improved more than the brisk walking group in the above outcomes (ps < 0.05). Conclusions: This study demonstrated the differential effects of Baduanjin exercise and brisk walking in middle-aged patients with schizophrenia. Baduanjin might be a beneficial regimen for improving physical and cognitive function in this population. Further research with a larger sample is warranted.